CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AS A CUSTOMER SATISFACTION AND RETENTION STRATEGY IN THE CHAIN RESTAURANT SECTOR - Ong Teenya Augustine; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
CSR is a comprehensive concept, encompassing companies' socially accountable activities, its social responsiveness, and its conducive efforts that are ultimately helpful to the society. This study aims to reveal the precise role of corporate social responsibility (CSR) within the customer retention method by considering the mediating impact of brand attitude, service quality, and customer satisfaction whereas work the moderating impact of brand love in the chain restaurant industry.The methodology used in this study is a quantitative method by distributing an online questionnaire consisting of 27 item statements with a five-point Likert-scale. The sample size used for this study was 225 people in Indonesia who are consumers of restaurants in Indonesia. This research data was processed using smartPLS 3.2.9 analysis tools and the research method in this study used Structural Equation Modeling (SEM) which is equation model with an approach based on variance or component-based structural equation modeling.The results of this study show that economic, ethical and philanthropic CSR are important factors to improve brand attitude and service quality. Interestingly, the aforesaid relationship helps increase customer retention. Our research outcomes also show that brand love indirect effects in moderating impact on the relationship between attitude and customer retention. This research provides the restaurant chain industry with a deeper understanding and valuable insights into the corporate social responsibility strategy of restaurant chain companies, and shows that specific corporate social responsibility measures have an impact on customer brand attitude and customer retention.